2021
DOI: 10.1016/j.annonc.2021.08.536
|View full text |Cite
|
Sign up to set email alerts
|

253P Risk factor (RF) identification (ID) and hyperglycemia (HG) prevention with alpelisib (ALP) + fulvestrant (FLV) in PIK3CA-mutated, hormone-receptor positive (HR+), human epidermal growth factor-2 negative (HER2-) advanced breast cancer (ABC)

Abstract: Background: A systematic literature review was conducted to summarize first-line (1L) treatments and clinical outcomes among patients with hormone receptor-positive (HR+), human epidermal growth factor 2-positive (HER2+) advanced or metastatic breast cancer (aBC).Methods: Clinical trials and real-world studies (RWS) published between 01/2000-12/ 2020 evaluating clinical outcomes of 1L treatments in adults with HR+/HER2+ aBC were identified through pre-specified searches in Medline, Embase, Cochrane Library, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…8 The authors found that the implementation of this protocol led to a reduction in grade 3-4 hyperglycemia events. 8 Lastly, a multicenter, phase II trial is ongoing to determine if metformin prophylaxis is effective in preventing hyperglycemia events with alpelisib in all patients regardless of risk factors. 9…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…8 The authors found that the implementation of this protocol led to a reduction in grade 3-4 hyperglycemia events. 8 Lastly, a multicenter, phase II trial is ongoing to determine if metformin prophylaxis is effective in preventing hyperglycemia events with alpelisib in all patients regardless of risk factors. 9…”
Section: Introductionmentioning
confidence: 94%
“…8 The authors found that the implementation of this protocol led to a reduction in grade 3-4 hyperglycemia events. 8 Lastly, a multicenter, phase II trial is ongoing to determine if metformin prophylaxis is effective in preventing hyperglycemia events with alpelisib in all patients regardless of risk factors. 9 Although the BYLieve trial gives insight into alpelisib + fulvestrant after a CDK4/6i, alpelisib + fulvestrant is commonly used as a salvage agent in the real-world setting due to prolonged efficacy of other first-line therapies and concerns of high rates of adverse effects.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Given the early onset and frequency of hyperglycemia associated with alpelisib, a pre-emptive approach to management is recommended. Although there is currently only limited evidence supporting this practice [ 44 ], metformin along with lifestyle changes can be considered for the prevention of alpelisib-induced hyperglycemia in prediabetic patients or high-risk patients with normal baseline glycemic status. According to a recent review by Anders et al, many oncologists initiate 500 mg of metformin extended release (XR) 7 days before starting alpelisib in high-risk patients [ 24 ].…”
Section: Preventive Management Strategies Before Starting Alpelisibmentioning
confidence: 99%